Are You Happy to Be a Farmer? Understanding Indicators Related to Agricultural Production and Influencing Factors: GAP-Şanlıurfa, Turkey - Aydoğdu, Mustafa Hakkı; Cançelik, Mehmet; Sevinç, Mehmet Reşit; Çullu, Mehmet Ali; Yenigün, Kasım; Küçük, Nihat; Karlı, Bahri; Ökten, Şevket; Beyazgül, Uğur; Doğan, Hatice Parlakçı; Sevinç, Gönül; Şahin, Zeliha; et al. (MDPI AG, 2021)
Recently, agricultural production areas and farmer numbers have been decreasing in Turkey, which has started to cause concern. This study aimed to analyze the satisfaction levels of farmers in different irrigation areas in the Southeastern Anatolia Project (GAP)-Şanlıurfa region, based on indicators related to agricultural production and influencing factors. The data were obtained through face-to-face surveys with farmers in 2020 and analyzed by logistic regression in STATA. According to the results, 43.3% of the farmers are happy to be farmers in the current situation, and 35.6% want their children to continue farming activities. It was determined that the area of irrigation, education level, income, and farming experience were statistically significant at different rates in terms of the happiness of the farmers. On the other hand, livestock, number of households, and land size were not statistically significant. While 27.5% of the participants were fully satisfied with the given public support, 15.7% were satisfied with the market selling prices of their products, and 43.5% stated that effective organizations are needed to live well. To ensure agricultural sustainability in the research area, there is a need for more agricultural support, effective extension services, and the development of rural tourism with the participation of the public and private sectors. This study was the first of its kind to be conducted in Turkey.
Keywords: farmer happiness; GAP-Şanlıurfa-Turkey; sustainable agricultural production; rural development; agricultural supports and extension; 2. Zero hunger; 1. No poverty; 12. Responsible consumption